Wide temperature-range, multi-component, optically isotropic antiferroelectric bent-core liquid crystal mixtures for display applications. Issue 3 (19th February 2018) - Wang, Junren; Bergquist, Leah; Hwang, Jung-Im; Kim, Kyeong-Jin; Lee, Joun-Ho; Hegmann, Torsten; Jákli, Antal
ABSTRACT: We present studies on 21 multi-component mixtures consisting of bent-core liquid crystals to obtain room temperature switching between optically isotropic and birefringent states. Four of the mixtures show a significant enhancement over our previous results that were obtained either only at elevated temperatures, or did not show switching at room temperatures with appreciable contrast or speed. Although the switching of the new mixtures still requires high fields and shows only speeds at ~100 ms, the results appear already useful for specific applications, such as transparent displays, that do not require video-rate switching and fast refresh rates of the content. GRAPHICAL ABSTRACT: